Epilepsy in Cerebral Palsy: Unraveling Prevalence, Risk Factors, and Subtype Associations in a Large-Scale Population Study - Reem Abdullah Alyoubi; Ahmed Abu-Zaid (Medicina)
Background and Objective: Cerebral palsy (CP) constitutes a group of enduring movement disorders arising from non-progressive brain damage, often accompanied by epilepsy. This study aims to explore the prevalence of epilepsy in CP patients, dissecting demographic characteristics, healthcare parameters, and nuanced risk factors. Materials and Methods: The study employed the National Inpatient Sample (NIS) database (2016–2019, four years). CP patients were identified through ICD-10 codes, excluding non-CP patients and those with missing values. Baseline characteristics of CP patients, such as age, subtype distribution, and types of epilepsy, were tabulated, and disparities were assessed using the chi-squared test. Univariate and multivariate logistic regression analyses were conducted to examine predictors of epilepsy according to CP subtypes and infant-related conditions. Data were presented as odds ratios (OR) with corresponding 95% confidence intervals (CI). Results: In this comprehensive analysis of 88,138 CP patients, 44,901 with epilepsy and 43,237 without epilepsy, disparities between those with and without epilepsy were uncovered, revealing distinct demographic patterns and healthcare characteristics. Spastic diplegic CP showed the strongest association with epilepsy (adjusted OR = 1.88, 95% CI [1.73–2.04], p < 0.0001), underscoring the significance of subtype-specific considerations. Perinatal infection emerged as a noteworthy risk factor for epilepsy development (adjusted OR = 1.61, 95% CI [1.17–2.23], p = 0.004). Conclusions: The study provides nuanced insights into the prevalence and associations of epilepsy in CP patients. Specific CP subtypes and perinatal factors play pivotal roles in epilepsy risk. These findings offer a foundation for tailored clinical management and support services, addressing the complex needs of individuals with CP and epilepsy.